PREDIKSI TEMPERATUR RESERVOAR PANASBUMI DENGAN MENGGUNAKAN METODA GEOTERMOMETER KIMIA FLUIDA - Yoga Aribowo (Diponegoro University, 2011)
In the preliminary study of Geothermal field development, one the most important thing to observe istemperature capacity of the geothermal reservoirs. One of several method to get subsurface temperature datathat low cost and reliable is geothermometry method. With just surface investigation of the geothermal prospectand fluid geochemistry analysis, it is possible to make a prediction how hot reservoir fluids are. The subsurfacetemperature prediction is based on physical and chemical properties of some chemical constituent. Temperaturedependant solubility of many chemical consituent of geothermal fluids such as silica, chloride, and Na.